Exploring The Gradual Islamization of Tana Toraja in South Sulawesi: History, Development, and Challenges - Michael, Anthonius; Masruri, Siswanto; Husein, Fatimah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The profound journey of Islam's expansion in South Sulawesi during the 15th century resulted in a gradual uptake of Islam within the Toraja region. This delayed acceptance, compared to other areas in South Sulawesi, is frequently attributed to the use of force during Islam's expansion. This perception highlights the challenge of promoting tolerance between the Muslim minority and Christian majority in the region. To understand the complexities of this phenomenon, this study seeks to explore factors beyond violence that contributed to the slow pace of Islamization. Employing a qualitative approach based in anthropology, the research delves into historical and cultural contexts. It finds that forceful Islamization efforts by figures like the Bone Kingdom, Kahar Muzakkar, and Andi Sose, actually hampered the spread of Islam due to the negative cultural impacts they created. Instead, it was the migration of Muslims to Toraja for trade that played a key role in introducing Islam to the region. Intermarriages further altered the dynamics, shifting Islamization from a conversion-focused approach to one based on family connections.  This had consequences for how Islamic communities developed, depending on the choices of second-generation Muslims. The slow pace of Islamization also influenced various aspects of social and religious life, leading the Toraja people to develop nuanced responses.  They managed change by emphasizing positive aspects of Islam while minimizing negative ones, aiming to maintain peace within their religiously diverse society.  Thus, the Toraja actively engaged in managing the evolving religious landscape, adapting their practices to maintain communal harmony.